Room temperature coercivities of Tb1-xDyxFe2 (110) molecular beam epitaxy grown films - Beaujour, J; Bowden, G; Zhukov, A; Rainford, B; de Groot, P; Ward, R; Wells, MR (2003)
The magnetic properties of a series of molecular beam epitaxially (MBE) grown (110) Tb1-xDyxFe2 alloy films on sapphire substrates were studied. All the measurements were performed at room temperature with the field applied along an in-plane axis. The difference between the bulk and MBE films is attributed to the presence of a magnetoelastic strain term, induced during crystal growth by the sapphire substrate.